Comparison of embryo quality and pregnancy outcomes for patients with low ovarian reserve in natural cycles and mildly stimulated cycles: a cohort study - Rui-Ying Yuan; Sen Li; Xie Feng; Xiao-Long Li; Xiao-ting Lin; Fu-min Gao; Hai-Jing Zhu; Yong-shi Li; Yan-chu Li; Xiang-Hong Ou (Taylor & Francis Group, 2024)
Background As women with low ovarian reserve embark on the challenging journey of in-vitro fertilisation (IVF) treatment, the choice between natural and mildly stimulated cycles becomes a pivotal consideration. It is unclear which of these two regimens is superior for women with low ovarian reserve. Our study aims to assess the impact of natural cycles on embryo quality and pregnancy outcomes in women with low ovarian reserve undergoing IVF treatment compared to mildly stimulated cycles.Methods This retrospective study enrolled consecutive patients with low ovarian reserve who underwent IVF/intracytoplasmic sperm injection (ICSI) at Guangdong Second Provincial General Hospital between January 2017 and April 2021. The primary outcome for pregnancy rate of 478 natural cycles and 448 mild stimulated cycles was compared. Secondary outcomes included embryo quality and oocyte retrieval time of natural cycles.Results The pregnancy rate in the natural cycle group was significantly higher than that in the mildly stimulated cycle group (51.8% vs. 40.1%, p = 0.046). Moreover, natural cycles exhibited higher rates of available embryos (84.1% vs. 78.6%, p = 0.040), high-quality embryos (61.8% vs. 53.2%, p = 0.008), and utilisation of oocytes (73% vs. 65%, p = 0.001) compared to mildly stimulated cycles. Oocyte retrievals in natural cycles were predominantly performed between 7:00 and 19:00, with 94.9% occurring during this time frame. In natural cycles with high-quality embryos, 96.4% of oocyte retrievals were also conducted between 7:00 and 19:00.Conclusion Natural cycles with appropriately timed oocyte retrieval may present a valuable option for patients with low ovarian reserve.